2022
DOI: 10.3390/traumacare2030034
|View full text |Cite
|
Sign up to set email alerts
|

Trends in State Anxiety during the Full Lockdown in Italy: The Role Played by COVID-19 Risk Perception and Trait Emotional Intelligence

Abstract: The COVID-19 pandemic is associated with mental health outcomes in the general population. This study assessed how state anxiety changed at different time points during the pandemic and how it was influenced by risk perception and trait emotional intelligence (trait EI). The study was conducted online in two data collections, at the beginning (wave 1, N = 1031) and at the end (wave 2, N = 700) of the lockdown. Participants were asked to self-report their state anxiety, risk perception of COVID-19 contagiousnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In this regard, individuals with high EI are expected to utilize emotional cues to direct attention and process emotions effectively. Consequently, these findings align with previous studies indicating that individuals with high EI may possess enhanced abilities and resources to effectively manage the emotional challenges presented by the pandemic [82][83][84][85].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this regard, individuals with high EI are expected to utilize emotional cues to direct attention and process emotions effectively. Consequently, these findings align with previous studies indicating that individuals with high EI may possess enhanced abilities and resources to effectively manage the emotional challenges presented by the pandemic [82][83][84][85].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, high EI individuals «may, therefore, have greater abilities and resources to adaptively navigate the emotional challenges posed by this pandemic» [82] (p. 1019). Trait EI people experienced anxiety less intensely during lockdown [83], and this tendency increased over time [84]. In addition, PEI was linked to effective coping strategies in dealing with government confinement measures [85].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…People who were experiencing the onset of the disease during the period of data collection (i.e., U.S., an early stage country) manifested increased “reasonable” fear (i.e., fear about exceeding the healthcare system’s capacity, and about not receiving treatments) to a greater extent than people in regions that had experiences, and where control measures had taken effect (in Hong Kong and Singapore) in the respective period. Indeed, as the pandemic progresses and risk perceptions change, the public’s anxiety levels adjust accordingly [ 39 ]. It is also important to note that our data do not shed any light on the optimal timing of the pandemic declaration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mechanisms underlying the onset of emotional stress reactions, a large number of studies have addressed the important role of risk perception on anxiety reactions, and some scholars have even suggested that risk perception plays an important role in each stage of anxiety response generation, presentation, and treatment 16 , 17 . An individual's perception of external objective risks can be referred to as risk perception, which emphasizes the influence of experiences based on intuitive judgments and subjective feelings on an individual's cognition 18 .…”
Section: Introductionmentioning
confidence: 99%